An innovative photoelectrochemical lab device for solar water splitting - Tânia Lopes (2014)
A photoelectrochemical (PEC) device capable of splitting water into storable hydrogen fuel by the direct use of solar energy is becoming a very attractive technology since it is clean and sustainable. Indeed, real field experiments are being developed in order to assess technological issues for large-scale usage under outdoor conditions. Following the need for developing photoelectrochemical devices with an optimized design that allows reaching a commercial performance level, the present works describes an innovative PEC cell for testing different photoelectrodes configurations, suitable for continuous operation and for easily collect the evolved gases. Moreover, a porous Teflons diaphragm useable for a wide range of aqueous electrolyte solutions is tested. Two semiconductors were investigated: tungsten trioxide and undoped hematite. The WO3 photoelectrodes were deposited in two different substrates: (i) anodized WO3 photoelectrodes on a metal substrate and (ii) WO3 deposited by blade spreading method on a TCO glass substrate. The undoped-Fe2O3 photoanode was deposited by ultrasonic spray pyrolysis technique in a TCO glass substrate. The material deposited on glass substrates allows to obtain transparent photoelectrodes. Photocurrent-voltage characteristics were obtained for all samples characterized under three different conditions: (i) no membrane separating the anode and the cathode evolution; (ii) using a Teflons diaphragm and (iii) using a Nafions 212 membrane. The transparent samples (photoanodes deposited on glass substrates) produced the highest values of photocurrent when the Teflons diaphragm was used. This photocurrent enhancement was assigned to the high reflectance showed by the diaphragm, which reflects back a significant fraction of the transmitted solar radiation.